A fast chemical approach towards Sb2S3 film with a large grain size for high-performance planar heterojunction solar cells. Issue 10 (27th February 2017) - Wang, Xiaomin; Li, Jianmin; Liu, Weifeng; Yang, Shangfeng; Zhu, Changfei; Chen, Tao
Abstract : A solar cell based on large grain Sb2 S3 film with high efficiency and stability is fabricated by a fast chemical approach. Abstract : A facile chemical method is developed for the fabrication of Sb2 S3 film with a lateral grain size as large as ∼12 μm. A solar cell based on this Sb2 S3 film achieves a power conversion efficiency of 4.3%, which is the highest value in solution processed planar heterojunction solar cells based on Sb2 S3 film.